Government checks and balances, policy credibility, and foreign direct investment: A cross-national investigation - Michael Touchton (Economies, 2023)
Placing constraints on elected officials is thought to bind their hands and render government policies credible. In turn, credible policies attract investment because investors can extend their policy and regulatory time horizons. Yet, a scholarship on LMICs suggests that too many constraints on policymakers may preclude necessary reforms, which repels capital. I motivate the study with an example from Liberia. Then, I evaluate political constraints and FDI for 182 countries between 1996 and 2022 and demonstrate that the rule of law conditions relationships between constraints on governments and FDI; in places with high rule of law, constraining government attracts FDI. In contrast, high constraints push investment away in contexts where the rule of law is lower. The logic is that constraining government makes credible high-income governments' previous commitments to property rights and contract enforcement. However, the very same constraints on government may prevent LMICs from making credible commitments in the first place. Constraining government thus prevents desirable reforms under many circumstances, which I illustrate by returning to the Liberia example in the discussion. Ultimately, this study raises questions about universal benefits emerging from policy credibility and extends our understanding of political institutions, credible commitment, and FDI
Keywords: 330; FDI; credible commitment; rule of law; property rights; investment